Crowing About Confidence: Technological Self-Efficacy in Academic Libraries - Chalifour, Joshua; Cmor, Dianne (Partnership, 2020)
Technological change is a constant in academic libraries and how we assess our ability to learn and use new technologies affects the services that we are able to provide. This article offers an introduction to the concept of technological self-efficacy and its potential relevance to library workers. It also provides a domain-specific measurement tool and ideas on how to build technological self-efficacy in library staff. We also talk about crows, because…the crow knows!